Chlorophyll concentration estimation using non-destructive methods in grapes (Vitis vinifera L.) cv. Riesling Becker - Castañeda, Cristian Santiago; Almanza-Merchán, Pedro José; Pinzón, Elberth Hernando; Cely, German Eduardo; Serrano, Pablo Antonio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Pigment analysis is a laboratory procedure and is not an immediate measurement to be performed in situ. The SPAD 502 and CCM-200 are equipments used for non-destructive, fast, and indirect estimates of chlorophyll contents. The concentration of photosynthetic pigments is related to the foliar concentration of nitrogen, so indirectly, it is possible to observe the deficiency or excess of this element, providing a technical basis to suggest the proper management of the crop in order to potentiate the photosynthetic efficiency, quality and yield of a vineyard. This research sought to compare measurements between the portable chlorophyll meter SPAD-502 vs. CCM-200 in the Riesling Becker grape variety under cold tropical climate conditions to determine the behavior of chlorophyll during the growth of leaves 4, 5 and 6, from flowering to harvest. The relationship between the measurements with the SPAD-502 and the CCM-200 were fit to a second degree polynomial determined with the equation for the Chlorophyll Concentration Index: CCI = 0.014SPAD2-0.2396SPAD + 5.8021. With a value of R2=0.9343 (n=96; P≤0.0001), which indicates that there was a high correlation between the portable equipment used in the present study to determine chlorophyll with a non-destructive method. The evaluations carried out with the equipment obtained fast and reliable measurements, with the choice of the moment of measurement according to the phenological stage of the plant being important because of the high variability in chlorophyll contents that are presented in relation to the phylotaxy.